Development of PARAPE (PKH people's market) Towards Prosperous Families in Cianjur District - Nurhidayat, Hikmat; Alijoyo, Franciskus Antonius (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2024)
Abstract should be written in English. The abstract, consists of no more than 200 words, should inform the readers briefly about the manuscript’s purpose, methods, findings, and values. References are not allowed to be cited in abstract. (Arial Narrow 10 Normal, Sentence Case)This study has determined the economic growth rate of the Hope Family Program (PKH) Beneficiary Family (KPM) in Cianjur Regency, whose marketing is supported by PARAPE (PKH People's Market) in Cianjur Regency. UMKMs can make a big difference in raising living standards, lowering unemployment, and promoting sustainable economic growth. Enhancing the efficacy and productivity of micro, small, and medium enterprises (UMKMs) is crucial for fostering social and economic well-being in the community. In many nations, including Indonesia, UMKMs form the backbone of the economy and play a major role in employment creation and regional and national economic growth. A component of the Indonesian government's initiatives to lessen social inequality and poverty in the nation is the Hope Family Program. Prosperous families are the outcome of similar initiatives that are implemented under other names and strategies in numerous other nations. One of the primary drivers of beneficiary families' transition from impoverished and at-risk to successful households is UMKMs. PARAPE has been successful in helping KPM use digitization to market KPM UMKM products. Additionally, it can motivate KPMs to graduate 10% of KPMs whose UMKM products are supported by PARAPE on their own.